Overcrowded : designing meaningful products in a world awash with ideas - Verganti, Roberto, ....- (Cambridge : MIT Press, 2016)
The standard text on innovation advises would-be innovators to conduct creative brainstorming sessions and seek input from outsiders -- users or communities. This kind of innovating can be effective at improving products but not at capturing bigger opportunities in the marketplace. In this book Roberto Verganti offers a new approach -- one that does not set out to solve existing problems but to find breakthrough meaningful experiences. There is no brainstorming -- which produces too many ideas, unfiltered -- but a vision, subject to criticism. It does not come from outsiders but from one person's unique interpretation.
Includes bibliographical references and index.
Keywords: New products; Product design; Design Thinking; Design